Implementation of HR management planning Solution Services Pharmaceutical Wholesaler Company (PBF) & Medical Devices (PAK), PT. Jagat Pharma Abadi - Erlangga, Deni; Syah, Tantri Rahmat; Hamdi, Edi; Septyanto, Dihin (Journal of Social Science, 2024)
Industry service health in Indonesia is very important important during life in the world still There is so service health still very much needed. This year budget Health in Indonesia has greatly improved. matter This chance big for business company big pharmaceuticals and tools health for supplying the needs of the house hospital Deni Erlangga, Tantri Rahmat Syah, Edi Hamdi, Dihin Septyantos, clinics and non- health institutions. The role of the company big pharmaceuticals and tools health this is very important to use meet the existing needs of each agency health. This research done for know how much big opportunity business This especially in Banten province and DKI Jakarta Province by using human resources in accordance with company characteristics. Research methods This use method qualitative by using technique studies literature and interviews and documentation. results from study This showing that for reach a specified target company must have human resources who have good abilities and analysis, p This For guard connection good with suppliers. role peting from a sales and marketing person is very supportive from sale. Conclusion on research This In order to achieve the company's targets, PT JPA strives increase quality from every employee. with the number such a budget big from government naturally This becomes very big opportunity for company, of course company must prepare talents employees who have capabilities in every field position work. No only PT JPA will to try increase abilities of each employee through training that will be given to every employee and of course level interesting career? for employees, p This to provide positive motivation? for employee for always increase performance his.